Analysis of Torsional Vibration Characteristic for the Crown Gear Coupling of EMU - Shi Zhenqiang; Xia Qinghua; Zhang Dezhi; Zhang Dianlong; Zhu Changping (Jixie chuandong)
The torsional vibration should be serious considered in the product design of the crown gear coupling of EMU. According to the structural characteristics and operating conditions of the crown gear coupling of EMU,the torsional vibration system mechanical model of the crown gear coupling is established by using lumped parameter method,and the differential equation of torsional vibration is established. The natural frequencies and the principal modes of system are obtained by solving the differential equation of torsional vibration. Moreover,considering time-varying meshing stiffness of inner and external teeth,the simplified calculation method for torsional stiffness of gear is presented. Finally,an example about analysis of torsional vibration for the coupling of EMU is given. The method of analysis of torsional vibration can provide some reference for vibration control and design of the crown gear coupling of EMU.